Tinjauan Resolusi Kebijakan Tentang Pembiayaan Usaha Kehutanan dan Pertanahan Dalam Menghadapi Perdagangan Bebas (AC-AFTA) dan Krisis Global - Rudi Hilmanto (Universitas Sultan Ageng Tirtayasa, 2013)
History notes that finances for Kredit Usaha Tani (KUT) on era 1997/1998 become problems namely of misfires credit. Now government issues to program finances as: Kredit Usaha Rakyat (KUR), Pembiayaan Pembangunan Kehutanan (P2H), and another type finances, to activity spur and productivity at agricultural sector, forest sector , and sector riil another. So is necessary policy resolution reviews finance at agricultural sector and forest to anticipate its negative impact. Fact refer that many constraint on finances at sector agricultural and sector forest another can evoke negative impact potency in the future. The research method use method Critical Multiplisme with analisis's area policy as multimedia's communication. Result of research indicate that policy resolution reviews finance at agricultural sector and forest now is: (1) farmer outonomy; (2) farming assurance and agrarian/farm conflict working outs; (3) price and buy assurance; (4) farming financeses even distribution and targets; (5) amenities to get credit facilities; (6) Sanctions; (7) Appreciate finances on region institute.